El comercio justo como una estrategia para el sistema de comercialización en el mercado La Esperanza de la ciudad de Riobamba. - Echeverría Padilla, Paulina Gabriela (2025)
The primary objective of this research was to investigate the impact of fair trade on the marketing system of the La Esperanza market, situated in the city of Riobamba. To achieve this objective, a quantitative approach and descriptive, explanatory, and field research methodology were used. Data collection was conducted through structured surveys with a sample of 243 merchants, which yielded relevant data on their economic, organizational, and commercial conditions. Data analysis was conducted using SPSS statistical software, employing descriptive techniques to assess the current situation and a nonparametric chisquare test to evaluate hypotheses. The results confirmed a significant influence of fair trade on the marketing system, which led to the acceptance of the alternative hypothesis (H1) and the rejection of the null hypothesis (H0). Based on these results, a proposal for strategies focused on implementing fair trade was developed, aimed at improving the organization, training, and working conditions of market participants. These strategies directly address the needs identified during the assessment and aim to promote a fairer, more supportive, and sustainable marketing system, benefiting local economic development.